2021
DOI: 10.1021/acsnano.1c07425
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Phase Growth of Cu Nanowires with Aspect Ratios Greater Than 1000: Multiscale Theory

Abstract: Penta-twinned metal nanowires are finding widespread application in existing and emerging technologies. However, little is known about their growth mechanisms. We probe the origins of chloride- and alkylamine-mediated, solution-phase growth of penta-twinned Cu nanowires from first-principles using multiscale theory. Using quantum density functional theory (DFT) calculations, we characterize the binding and surface diffusion of Cu atoms on chlorine-covered Cu(100) and Cu(111) surfaces. We find stronger binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 59 publications
(151 reference statements)
1
17
0
Order By: Relevance
“…Moreover, plates can take on a variety of shapes during growth: from triangular and truncated triangular to round and hexagonal. Though the diffusion of Cu atoms is slower on I-covered Cu(111) than on the bare surface, 46 it is still relatively rapid and, as we showed in our absorbing Markov chain calculations, it is rapid enough to promote lateral growth of microplates with dimensions in the 1–10 micron range. Therefore, we conclude the adsorption of iodine on Cu surfaces favors the anisotropic growth of thin Cu plates by influencing on both seed formation and growth stages.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Moreover, plates can take on a variety of shapes during growth: from triangular and truncated triangular to round and hexagonal. Though the diffusion of Cu atoms is slower on I-covered Cu(111) than on the bare surface, 46 it is still relatively rapid and, as we showed in our absorbing Markov chain calculations, it is rapid enough to promote lateral growth of microplates with dimensions in the 1–10 micron range. Therefore, we conclude the adsorption of iodine on Cu surfaces favors the anisotropic growth of thin Cu plates by influencing on both seed formation and growth stages.…”
Section: Discussionmentioning
confidence: 61%
“…42,43 We used (and explained) this method in prior work. [44][45][46] Briey, we solve for the average time, considering all possible deposition sites, for a Cu atom deposited on a basal {111} facet to diffuse to a side facet. This involves constructing a Markov matrix to characterize the network of diffusion rates for site-to-site hops/exchanges.…”
Section: Lateral Vs Vertical Growth Of Cu Microplatesmentioning
confidence: 99%
“…In this case, the established Ag 0 reduction rate for growing AgNRs is too higher than that for the growth of AgNWs at a less concentration of seed. Therefore, a lower reduction rate of Ag 0 might be able to satisfy the further longitudinal growth of AgNRs. , For this reason, HNO 3 was introduced into the AgNR seeding solution to lower the pH value and decrease the reaction kinetics for forming Ag 0 by attenuating the reducing capability of AA. To minimize the effects of other experimental conditions, the nominal concentrations of each chemical added are very close to those established in preparing AgNR seeds.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, asymmetry in adatom diffusion can be described by the Boltzmann factor e Δ/ k B T , where Δ = E down – E up . For bare fcc surfaces, Δ > 0 because they exhibit greater rates of {111}-to-{100} diffusion than the reverse. , However, modifications to bare fcc surfaces, such as by surface ligands and lattice strain, have been shown to influence surface dynamics. , XPS showed that our Au nanorods were not bare during solution-phase growth but covered, including sparsely with Cl (Figure S8a). Our experiments were then analogous to the solution-phase growth of Cl-covered pentatwinned nanorods composed of another fcc metal, Cu, for which DFT calculations predict that {100}-to-{111} interfacet diffusion predominates (Δ < 0) .…”
Section: Resultsmentioning
confidence: 99%
“…Our experiments were then analogous to the solution-phase growth of Cl-covered pentatwinned nanorods composed of another fcc metal, Cu, for which DFT calculations predict that {100}-to-{111} interfacet diffusion predominates (Δ < 0). 65 To examine if Cl controlled the extent of anisotropic growth or if it was supersaturation as indicated in Figure 3h,i, we replaced HCl with 160 equiv of HNO 3 in the growth formulation. This reaction yielded only nanodecahedra and low-AR nanorods as the pentatwinned products (Figure S35), with supersaturation dynamics comparable to the reaction with 40 equiv of HCl (Figure 3f); both results were consistent with the lesser influence of only H + when compared to that of both H + and Cl − to the supersaturation dynamics (Figure S6a).…”
Section: T H Imentioning
confidence: 99%